The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.31219/osf.io/z7ypk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microstructure Characteristic and Compressive Strength of Self Compacting Concrete Using Sea Water as Mixing Water

Abstract: Indonesia is an archipelagic country which makes many areas doesn't have qualified water as drinking water. As concrete construction building in the region has possibly minimum or non-existent amount of fresh water, the using of sea water in mixing concrete and curing concrete is unavoidable. The demand of water is getting more and more increasing in both the improvement of infrastructure development and the life need. In the concrete industry, several billion tons of water is used as water mixing, curing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…These studies demonstrate the feasibility of producing seawater-mixed SCC which satisfies the existing guidelines for SCC, although the seawater slightly decreases the workability of fresh SCC, similar to the case for conventional concrete [61]. The compressive and tensile strengths of seawater-mixed SCC were found to be generally higher than those of the corresponding freshwater-mixed SCC even at later ages, especially when a large amount of fly ash is used in the mixture [61,62,65]. As suggested by the other studies, this enhancement could be due to the synergistic effects between seawater and SCMs.…”
Section: Self-compacting Concrete (Scc)supporting
confidence: 63%
See 2 more Smart Citations
“…These studies demonstrate the feasibility of producing seawater-mixed SCC which satisfies the existing guidelines for SCC, although the seawater slightly decreases the workability of fresh SCC, similar to the case for conventional concrete [61]. The compressive and tensile strengths of seawater-mixed SCC were found to be generally higher than those of the corresponding freshwater-mixed SCC even at later ages, especially when a large amount of fly ash is used in the mixture [61,62,65]. As suggested by the other studies, this enhancement could be due to the synergistic effects between seawater and SCMs.…”
Section: Self-compacting Concrete (Scc)supporting
confidence: 63%
“…As suggested by the other studies, this enhancement could be due to the synergistic effects between seawater and SCMs. Microstructural investigations of seawater-mixed SCC have also been performed [62][63][64] and effects of curing methods on strength development in SCC have been explored [61]. Raidyarto et al (2020) demonstrated the feasibility of producing seawater SCC with steel fibers; although corrosion was not explored in this study [66].…”
Section: Self-compacting Concrete (Scc)mentioning
confidence: 97%
See 1 more Smart Citation